Knowledge of midwives on the hospital infections in terms of insertion and care of peripheral needles - Kołodziej, Bernadeta; Barnaś, Edyta; Wróbel, Romana; Kremska, Anna (Nursing in the 21st Century, 2013)
KNOWLEDGE OF MIDWIVES ON THE HOSPITAL INFECTIONS IN TERMS OF INSERTION AND CARE OF PERIPHERAL NEEDLES Introduction. Nosocomial infections are a great problem in hospitals in most of countries and despite development of methods of their control, they are still present at quite high level. It necessitates possessing well-defined procedures and their implementation by well-trained personnel and also monitoring their effectiveness. Aim. The aim of this work was to determine midwives’ knowledge in scope of hospital-acquired infections in the context of inserting and caring for peripheral insertions. Material and method. The study group consisted of 96 midwives employed in hospitals in the Podkarpackie region . The study was performed using a diagnostic survey based on the authors’ questionnaire. The research was performed from November 2009 to February 2010. The results were processed using statistical program Statistica 8.0 and Chi² Test. Results. Most midwives did not complete the course for nosocomial infections. Only half of the respondents know the correct technique of blood vessel catheterization. Midwives after graduation from undergraduate studies stated that the nosocomial infection is a clinical diagnosis and a laboratory-confirmed infection that occurs during hospitalization and is revealed during the patient’s stay in hospital; the same responses were given by people after graduation from medical post-secondary school (p = 0.05). Among the respondents, 85% of midwives always use single-use gloves when setting vascular catheters, which may be related to the fact that have not registered a catheter infection p = 0.0003). Conclusions. Knowledge of many midwives on hospital infections is inadequate. Consequently, it is necessary to have a higher level of education on the causes and prevention of nosocomial infections, especially on catheter-related infections. It is necessary to conduct regular training on hospital infections in any health care institution.